2011
DOI: 10.1021/cg200387n
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Characterization of Diamond from Carbonyl Iron Catalyst under High Pressure and High Temperature Conditions

Abstract: Crystal Growth & Design ARTICLE diffusion on diamond crystallization and provides a lot of valuable information on the search for the genesis of natural diamond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Additionally, the presence of the diamond slices could be attributed to the simultaneous incorporation of the oxygen and nitrogen atoms into the diamond lattice structure. The result is very good agreement with the last report [11].…”
Section: Inclusions and Morphology Of The Synthesized Diamondsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, the presence of the diamond slices could be attributed to the simultaneous incorporation of the oxygen and nitrogen atoms into the diamond lattice structure. The result is very good agreement with the last report [11].…”
Section: Inclusions and Morphology Of The Synthesized Diamondsupporting
confidence: 93%
“…Recently, diamonds with special habits were synthesized using carbonyl iron powders as catalyst by film growth under high pressure and high temperature (HPHT) conditions and the synthesized crystals were 0.3-0.8 mm in size [11]. It is well known that temperature gradient growth (TGG) is an effective approach to get large size single diamonds.…”
Section: Introductionmentioning
confidence: 99%
“…The role of Fe catalyst in this approach is to enhance diamond nucleation as previously demonstrated by several studies. [82,83] These diamond nanowires are straight, thin, and long over tens of micrometers with a high crystallinity and structural uniformity ( Figure 2g,h). [77] Another main advantage of the bottom-up method based on the VLS process is in situ doping by incorporating desired dopant precursors in the synthesis procedure.…”
Section: Synthesis and Growth Of Bottom-up Nanowiresmentioning
confidence: 99%
“…Nitrogen, which is an omnipresent impurity in synthetic and natural diamonds, has been shown to drastically influence diamond growth process and lead to significant changes in the real structure and properties of diamond crystals. 7 9 It has been shown that the addition of small amounts of H 2 O to the metal–carbon systems gives rise to the impurity adsorption effect on diamond growth and leads to the formation of specific antiskeletal crystals. 10 , 11 An increase in the H 2 O content in the growth system leads to a decrease in the nitrogen content in diamonds and the appearance of hydrocarbon inclusions.…”
Section: Introductionmentioning
confidence: 99%